INDONESIA IS THE BIGGEST GRANT OF OIL PALM CRUDE PALM OIL (CPO) IN THE WORLD BUT FACING THE PROBLEM OF OIL SCARCITY SURPRISE COOKING OIL PRICES - Junaedi Junaedi (International Journal of Social Science, 2022)
Indonesia is a granary for palm oil, so being the largest producer of crude palm oil (CPO) in the world, it is still faced with the problem of oil scarcity, so that cooking oil prices spike. Indonesia Is A Palm Oil Barn, So Being The Largest Producer Of Crude Palm Oil (CPO) In The World Still Faced With The Problem Of Oil Scarcity Surge In Cooking Oil Prices, The purpose of this study is expected to be able to study and analyze Indonesia is a Palm Oil Barn, so that it becomes the Largest Producer of Crude Palm Oil (CPO) The world is still faced with the problem of oil scarcity, cooking oil prices spike. Data analysis was carried out using an analysis based on Indonesia as a Palm Oil Barn, so that it becomes the Largest Producer of Crude Palm Oil (CPO) in the World Still Faced with the Problem of Oil Scarcity, Cooking Oil Price spikes. Being the Largest Producer of Crude Palm Oil (CPO) in the World Still Faced with the Problem of Oil Scarcity, Spike in Cooking Oil Prices. As for the benefits of this research Academically, this research is useful related to Indonesia is a Palm Oil Barn, so that it becomes the Largest Producer of Crude Palm Oil (CPO) in the World Still Faced with the Problem of Oil Scarcity, Surge in Cooking Oil Prices, while Theoretically, this research can enrich the repertoire of literature in In the study, Indonesia is a palm oil barn, so that it becomes the largest producer of Crude Palm Oil (CPO) in the world. It is still faced with the problem of oil scarcity. Cooking oil prices spike.